The Use Of Content Marketing To Improve The Sharing Economy - Feronica Simanjorang; Rahma Hayati Harahap (International Journal of Business and Quality Research, 2023)
The purpose of this study is to analyze the issues and challenges in implementing and adopting the sharing economy concept. More specifically, the paper intend to identify how CM can maximize the implementation of the sharing economy concept in tourism industries of the Lake Toba region. The type of research used is qualitative with a descriptive approach. Data were obtained by means of observation, documentation, and in-depth interviews with the communities and entrepreneurs who have been applied the sharing economy concept and have implemented CM on different social media platforms. The study identified three critical factors of CM that influence the implementation of the share economy concept in Lake Toba region, namely, relevant to current market, trust and engagement. The researcher suggested that entrepreneurs in the Lake Toba tourism industry add CM, especially short videos, to their business strategy.